1970
DOI: 10.1139/p70-155
|View full text |Cite
|
Sign up to set email alerts
|

The 4550 Å band system of glyoxal. II. Vibration–rotational analyses for 12 bands of C2H2O2

Abstract: Rotational analyses have been performed for 12 bands of the 1Au–1Ag (π*–n) transition of glyoxal. Approximately 15 000 lines have been assigned, and rotational and vibrational constants obtained by computer methods. The vibrations investigated are ν2′ (CO stretching), ν4′ (C–C stretching), ν5′ and ν5″ (CCO bending), and the torsional levels with ν7 ′ = 1–4 and ν7″ = 1–3. A Coriolis interaction has been found involving the vibrations ν7 (au) and ν12 (bu). Some weak anharmonic interactions have also been identif… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
30
2

Year Published

1974
1974
1997
1997

Publication Types

Select...
9
1

Relationship

4
6

Authors

Journals

citations
Cited by 112 publications
(33 citation statements)
references
References 0 publications
1
30
2
Order By: Relevance
“…The identity of the molecule responsible for the new bands was not established, however, until one of the bands near 4875 A was photographed in absorption with high resolution anda rotational analysis was carried out (CURmE and RA~SAY [1]). The rotational constants were clearly incompatible with those which had been obtained for trans glyoxal (PALDUS and I:{AMSAY [3], BIRSS et al [4]) but were reasonable for a cis molecule. The analysis shows that the band has a type C rotational structure consistent with an AT1B1 --:~lA 1 (~* --n) transition.…”
Section: Introductioncontrasting
confidence: 61%
“…The identity of the molecule responsible for the new bands was not established, however, until one of the bands near 4875 A was photographed in absorption with high resolution anda rotational analysis was carried out (CURmE and RA~SAY [1]). The rotational constants were clearly incompatible with those which had been obtained for trans glyoxal (PALDUS and I:{AMSAY [3], BIRSS et al [4]) but were reasonable for a cis molecule. The analysis shows that the band has a type C rotational structure consistent with an AT1B1 --:~lA 1 (~* --n) transition.…”
Section: Introductioncontrasting
confidence: 61%
“…Figure 2 shows medium resolution laser-induced fluorescence spectra of the electronic origin of aniline [20] M=A(pD/atmcm) o'~ with A=148 for Ne [21] and A=133 for Ar [20,21]. The rotational temperatures T R in pulsed jets were determined by fitting the rotational contours of figure 2 by computer-simulated contours of aniline [22], which were generated using the asymmetric-rotor computer programme of Birss and Ramsay [23,24] and utilizing the rotational constants of Christoffersen et al (vapour pressure 0-3 Torr) was seeded into Ne at the stagnation pressures indicated on the curves and expanded through a 600/~m nozzle. The laser crossed the jet at x=15 mm.…”
Section: Cooling Of Aniline In Supersonic Expansionsmentioning
confidence: 99%
“…The 4550 A band is the 0-0 band of the A~A,-X'A, (.sr:%-n) system of trans-glyoxal. Many other bands in this system for C2H,O2, C'HDO,, C2D202, and 1 3~2~2 0 2 have been rotationally analysed (3)(4)(5)(6), giving accurate rotational and vibrational constants for levels in the ground and excited states and also permitting a detennination of the geometric structures in both states.…”
Section: Introductionmentioning
confidence: 99%